Microwave-assisted synthesis of iridium oxide and palladium nanoparticles supported on a nitrogen-rich covalent triazine framework as superior electrocatalysts for the hydrogen evolution and oxygen reduction reaction - Rademacher, Lars; Beglau, Thi Hai Yen; Heinen, Tobias; Barthel, Juri; Janiak, Christoph (Frontiers in Chemistry, 2022)
Iridium oxide (IrOx-NP) and palladium nanoparticles (Pd-NP) were supported on a 2,6-dicyanopyridine-based covalent-triazine framework (DCP-CTF) by energy-saving and sustainable microwave-assisted thermal decomposition reactions in propylene carbonate and in the ionic liquid [BMIm][NTf2]. Transmission electron microscopy (TEM), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) confirm well distributed NPs with sizes from 2 to 13 nm stabilized on the CTF particles. Metal contents between 10 and 41 wt% were determined by flame atomic absorption spectroscopy (AAS). Nitrogen sorption measurements of the metal loaded CTFs revealed Brunauer–Emmett–Teller (BET) surface areas between 904 and 1353 m2 g-1. The composites show superior performance towards the hydrogen evolution reaction (HER) with low overpotentials from 47 to 325 mV and towards the oxygen reduction reaction (ORR) with high half-wave potentials between 810 and 872 mV. IrOx-samples in particular show high performances towards HER while the Pd-samples show better performance towards ORR. In both reactions electrocatalysts can compete with the high performance of Pt/C. Exemplary cyclic voltammetry durability tests with 1000 cycles and subsequent TEM analyses show good long-term stability of the materials. The results demonstrate the promising synergistic effects of NP-decorated CTF materials resulting in a high electrocatalytic activity and stability.